Vasopressin differentially modulates the excitability of rat olfactory bulb neuron subtypes - Suyama, Hajime; Bianchini, Gaia; Lukas, Michael (Frontiers in Neural Circuits, 2024)
Vasopressin (VP) is essential for social memory already at the level of the olfactory bulb (OB), and OB VP cells are activated by social interaction. However, it remains unclear how VP modulates olfactory processing to enable enhanced discrimination of very similar odors, e.g., rat body odors. So far, it has been shown that VP reduces firing rates in mitral cells (MCs) during odor presentation in-vivo and decreases the amplitudes of olfactory nerveevoked excitatory postsynaptic potentials (ON-evoked EPSPs) in external tufted cells in-vitro.We performed whole-cell patch-clamp recordings and population Ca 2+ imaging on acute rat OB slices. We recorded ON-evoked EPSPs as well as spontaneous inhibitory postsynaptic currents (IPSCs) from two types of projection neurons, middle tufted cells (mTCs) and MCs.VP bath-application reduced the amplitudes of ON-evoked EPSPs and the frequencies of spontaneous IPSCs in mTCs but did not change those in MCs. Therefore, we analyzed ON evoked-EPSPs in inhibitory interneurons, i.e., periglomerular cells (PGCs) and granule cells (GCs), to search for the origin of increased inhibition in mTCs. However, VP did not increase the amplitudes of evoked EPSPs in either type of interneurons. We next performed twophoton population Ca 2+ imaging in the glomerular layer and the superficial GC layer of responses to stronger ON stimulation than during patch-clamp experiments that should evoke action potentials in the measured cells. We observed that VP application increased ON-evoked Ca 2+ influx in juxtaglomerular cell and GC somata. Thus, our findings indicate inhibition by VP on projection neurons via strong ON input-mediated inhibitory interneuron activity.